2019
DOI: 10.1111/bjh.16263
|View full text |Cite
|
Sign up to set email alerts
|

New prognosis score including absolute lymphocyte/monocyte ratio, red blood cell distribution width and beta‐2 microglobulin in patients with diffuse large B‐cell lymphoma treated with R‐CHOP: Spanish Lymphoma Group Experience (GELTAMO)

Abstract: Summary The International Prognostic Index (IPI) is the most widely used score for non‐Hodgkin lymphoma but lacks the ability to identify a high‐risk population in diffuse large B‐cell lymphoma (DLBCL). Low absolute lymphocyte count and high monocytes have proved to be unfavourable factors. Red‐cell distribution width (RDW) has been associated with inflammation and beta‐2 microglobulin (B2M) with tumour load. The retrospective study included 992 patients with DLBCL treated with R‐CHOP. In the multivariate anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 36 publications
3
67
0
Order By: Relevance
“…High monocyte count and low lymphocyte count indicate increased mortality and declined prognosis in a variety of disorders. 21 It's reported that LMR is a highly sensitive analyzing item used for diagnosis of diabetes, 22 large B-cell lymphoma, 23 cardiovascular diseases, 21 , 24 , 25 and COVID-19, 26 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…High monocyte count and low lymphocyte count indicate increased mortality and declined prognosis in a variety of disorders. 21 It's reported that LMR is a highly sensitive analyzing item used for diagnosis of diabetes, 22 large B-cell lymphoma, 23 cardiovascular diseases, 21 , 24 , 25 and COVID-19, 26 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…33 In general, pathological examination of suspicious tissue obtained from a biopsy or resection is considered as the gold standard procedure for definitive diagnosis when the intracranial lesion is uncertain, whereas CT and MRI are the important supplemental diagnostic approaches for assistance of diagnosis, tumor staging, and evaluation of therapeutic efficacy. 9 However, both the neuroimaging tests and pathological examination are expensive with limited sensitivity, even at risk of hemorrhage and neurologic impairment, which have greatly limited their application for the clinical differential diagnosis. 10 Thus, there is an urgent need for the low cost, easily obtained, and minimally invasive markers with improved diagnostic sensitivity and specificity for patients with HGG and sBM.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recently, the clinical application values of serum β2-microglobulin (β2-m) in predicting prognosis and monitoring of therapeutic efficacy has been rapidly highlighted. 9 Several studies have shown an increased level of β2-m in solid tumors, including lung cancer and gastrointestinal cancer. [10][11][12] However, the expression of β2-m in HGG and sBM remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Beta-2 microglobulin is a small polypeptide light chain that forms part of the major histocompatibility complex class I antigens. As white-blood-cell membrane turnover is the primary source of serum beta-2 microglobulin, elevated serum betamicroglobulin levels have been associated with lymphoid malignancies with significant tumour burden, high rates of cellular turnover and more invasive potential [4].…”
Section: Lactate Dehydrogenase Beta-2 Microglobulin Levels and Cd4/cmentioning
confidence: 99%